1998
DOI: 10.1021/jo9718612
|View full text |Cite
|
Sign up to set email alerts
|

New Intramolecular α-Arylation Strategy of Ketones by the Reaction of Silyl Enol Ethers to Photosensitized Electron Transfer Generated Arene Radical Cations:  Construction of Benzannulated and Benzospiroannulated Compounds

Abstract: Efficient intramolecular α-arylation of ketones is achieved by the reaction of silyl enol ethers to photosensitized electron transfer (PET) generated arene radical cations. The arene radical cations are generated by one-electron transfer from the excited state of the methoxy-substituted arenes to ground-state 1,4-dicyanonaphthalene (DCN). This arylation strategy has provided the unique opportunity of constructing five- (23), six- (18), seven- (25) and eight-membered (27) benzannulated as well as benzospiroannu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…142 Thus, for reactions whose efficiencies suffer from BET, the triplet state of the photoredox catalyst may be the most important excited state. 147 Under aerobic conditions using DCN as the single electron photooxidation catalyst, a range of different cyclization modes were possible to form 5−8 membered ring systems via both endo-(6.1, 6.3) and exo-(6.5, 6.7)-type annulations (Scheme 6). All of the aromatics investigated in the transformations bore either one or two methoxy substituents, seemingly a requirement for successful cyclization.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…142 Thus, for reactions whose efficiencies suffer from BET, the triplet state of the photoredox catalyst may be the most important excited state. 147 Under aerobic conditions using DCN as the single electron photooxidation catalyst, a range of different cyclization modes were possible to form 5−8 membered ring systems via both endo-(6.1, 6.3) and exo-(6.5, 6.7)-type annulations (Scheme 6). All of the aromatics investigated in the transformations bore either one or two methoxy substituents, seemingly a requirement for successful cyclization.…”
Section: Definitionsmentioning
confidence: 99%
“…147 It is presumed that oxidation of the alkyl selenides 8.1 outcompetes the silyl enol ether (8.2) oxidation due to a more exergonic electron transfer event (cf. ΔG ET = −10.8 kcal mol −1 for 8.2 and −13.0 kcal mol −1 for 8.1).…”
Section: Definitionsmentioning
confidence: 99%
“…The photoaddition product 6a is formed by sequential SETdesilylation pathways and exists as diastereomers in ca. 1 to 1.4 ratios according to 1 H-NMR and 13 C-NMR spectra data. IR spectra of photoaddition products 6a and 7a show characteristic absorption bands for hydroxyl group at 3000-3600 cm −1 and carbonyl group at 1650-1710 cm show singlet peaks at 2.55-3.52 ppm for methyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 The study on the SET photochemistry of the easily oxidized trimethylsilyl enol ether have shown that photoinduced SET occurs from a simple trimethylsilyl enol ether to generate an intermediate cation radical, which is converted into the precursor aldehyde or ketone. [11][12][13] In this research, the SET-induced photochemical reaction of silyl enol ether (5a-d) with N-methylphthalimide (1) was investigated. The results of this efforts, reported below, show that N-methylphthalimide with cyclic silyl enol ether as an electron donor undergoes photoaddition reaction exclusively via SET-desilylation pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Aryl radical cations generated by electron-transfer processes from methoxy substituted arenes to DCN, tethered by oxygen, nitrogen as well as carbon nucleophile leads to intramolecular cyclizations (Scheme 8.67). The synthetic potentials of Phenyl vinyl sulfone 75 this strategy have been exploited for the formation of aromatic five-membered heterocyclic derivatives 243 and 245 [106], benzofurans [106], and indanes 247 [107]. The PETactivation of SiÀSi bond possessing compounds such as 248 using excited DCA as an electron acceptor is reported to lead its dissociation, followed by intramolecular trapping of the resultant cation to produce the corresponding cyclic silyl ethers 249 in 45-78% yield, as depicted in Scheme 8.68 [108].…”
Section: Photoinduced Electron Transfer-mediated Cyclizations J273mentioning
confidence: 99%